Extending the theory of planned behaviour: Spiritual values and social norms as drivers of sustainable behaviour among university students in Malaysia - Hassan, Norhasliza; Abdul Mokti, Hawwa (Journal of Islamic, Social, Economics and Development, 2025)
University students are often viewed as key agents of change in advancing sustainability, however, their everyday behaviour does not always reflect their environmental awareness. Despite widespread sustainability campaigns and educational initiatives, the translation of knowledge and positive attitudes into consistent sustainable behaviour remains limited. Drawing on the Theory of Planned Behaviour (TPB), this study extends the framework by examining the role of spiritual values and subjective norm in shaping sustainable behaviour among students of public universities in Malaysia. Using a quantitative cross-sectional design, data were collected from 956 students and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings indicate that both spiritual values and subjective norm significantly influence sustainable behaviour, with spiritual values exerting a stronger effect. This suggests that internal value-based motivations play a crucial role in guiding sustainable actions beyond cognitive understanding and social pressure alone. By incorporating spiritual values into TPB, this study offers a more holistic perspective on sustainable behaviour in higher education and provides practical insights for designing values-oriented sustainability education and interventions.